Proof of office in constitutional democracy - Cupe Calcina, Eloy Marcelo (2019)
A fundamental aspect of the Constitutional Democracy is the Jurisdiction, this one demands the Judge to know the Law and the facts; knowing the facts implies establishing the truth in correspondence with reality, without it you can not reach a just decision; therefore, in a Constitutional Democratic State, the Judge can not stop trying to reach the reality of the facts and, the essential object of every process is the search for the truth. If it has been legally chosen to give the Judge the power to dispose the action of proof ex officio, the exercise of this power is guaranteed by the Constitution itself.